2020
DOI: 10.3389/fenvs.2020.591695
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Soil Functions: An Example of Meeting Competing National and International Obligations by Harnessing Regional Differences

Abstract: The increased demand for bio based products worldwide provides an opportunity for Eastern European countries to increase their production in agriculture and forestry. At the same time, such economic development must be congruent with the European Union’s long-term climate and biodiversity objectives. As a country that is rich in bioresources, the Latvian case study is highly relevant to many other countries—especially those in Central and Eastern Europe—and faces a choice of transition pathways to meet both ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 84 publications
(109 reference statements)
0
23
0
Order By: Relevance
“…Among micronutrients, horticultural crops suffer from Zn deficiency worldwide, especially in calcareous soils, but also in light sandy and peaty soils [ 41 ]. Such agricultural soils are typical for Latvia as well [ 42 ]. Studies on different strawberry cultivars and most recommendations for sufficiency levels indicated that Zn deficiencies in strawberries were associated with leaf concentrations below 20 mg kg −1 [ 9 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among micronutrients, horticultural crops suffer from Zn deficiency worldwide, especially in calcareous soils, but also in light sandy and peaty soils [ 41 ]. Such agricultural soils are typical for Latvia as well [ 42 ]. Studies on different strawberry cultivars and most recommendations for sufficiency levels indicated that Zn deficiencies in strawberries were associated with leaf concentrations below 20 mg kg −1 [ 9 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…A formula was suggested for calculating the ecological scores of soils, these scores were calculated on the basis of the ratio of the plant to the appearance degrees of the separate soil signs. At present, numerous studies are being carried out all over the world in this direction, where methodological approaches to assessing the ecological state of soils are being improved [15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In 1990, the restructuring process led to fundamental changes in the structure of Latvian agriculture, namely (1) changes in land ownership and (2) the redistribution of fixed assets of large collective farms to private farms (Strīķis, 1997). These changes led to the collapse of agricultural activity with a decrease in the amount of agricultural land and livestock (Valujeva et al, 2020), and the abandonment of about 11% of agricultural land (Nipers, 2019). This lasted until Latvia joined the European Union in 2004 and benefitted from support payments of the Common Agricultural Policy (Zdanovskis and Pilvere, 2015).…”
Section: Case Studiesmentioning
confidence: 99%
“…In a previous study (Valujeva et al, 2020), we identified the supply and demand for three soil functions relevant to Latvia's agro-climatic conditions; namely, primary productivity (PP), carbon regulation (CR), and habitat for biodiversity (BD), using European and Latvian policies to guide the quantification of demand for soil functions, and the gradient from mineral to histic soils and land use for the quantification of supply of these same soil functions. In that paper, we explained the parameterisation of the demand for PP through the combination of regional bioeconomy GDP targets and unemployment rates at the municipal level using the tabular index approach by Greiner et al (2018).…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation